Results of Anthropometric Examinations of The Maxillofacial Region of Children With Adenoids - N.P. Alimova (American Journal of Botany and Bioengineering, 2024)
Under the influence of the environment, the transformation of the development of the organism in growth develops, which reflects the physical development. The morphometry of physical development is reflected in the indicators of anthropometry, physiognometry and data of functional activity. Height, weight and chest circumference are the main anthropometric parameters of physical development of children at certain stages of ontogenesis.